Scaling laws for gas-solid riser flow through two-fluid model simulation - Naren, P. R.; Ranade, Vivek. V. (Particuology, 2011)
Scale up of gas-solid circulating fluidized bed (CFB) risers poses many challenges to researchers. In this paper, CFD investigation of hydrodynamic scaling laws for gas-solid riser flow was attempted on the basis of two-fluid model simulations, in particular, the recently developed empirical scaling law of Qi, Zhu, and Huang (2008). A 3D computational model with periodic boundaries was used to perform numerical experiments and to study the effect of various system and operating parameters in hydrodynamic scaling of riser flow. The Qi scaling ratio was found to ensure similarity in global parameters like overall cross-sectional average solid holdup or pressure drop gradient. However, similarity in local flow profiles was not observed for all the test cases. The present work also highlighted the significance of error bars in reporting experimental values. (C) 2010 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights reserved.
Keywords: CFD; Error bar; Periodic boundary; Risers; Scaling; Two-fluid model